I am Because We Are: - Jesse Ford; Dwayne Hamilton, Jr; Alexis Moore; Jordan Farmer; Ashley Billie; Kameryn Taylor (Journal of College Orientation, Transition, and Retention, 2022)
Despite the fact that more Black students than ever pursue graduate education, the experiences of Black graduate students in higher education and student affairs programs leave much to be discovered. This work aims to shed light on the interconnections of Black students in higher education and master's programs in student affairs, as well as the impact of peer mentoring on their transition to graduate school. This scholarship concludes with recommendations for assisting this population's growth at the outset of their academic careers.